Urgensi Penerapan E-Katalog Terhadap Pelaksanaan Pemilihan Pengadaan Barang/Jasa Melalui Penyedia - Hendrio, Hendrio (Prosiding, 2024)
This research aims to find out and understand the Urgency of Implementing e-Catalogs in the Implementation of Selection of Procurement of Goods/Services Through Providers (Empirical Study in the Kampar Regency Regional Government) which is one of the Planned Methods for Selection of Providers at the Planning stage of Procurement of Goods/ Services as well as an assessment of performance of the procurement of goods/services based on the opinions of the public and procurement actors (non-providers and providers) with the aim of knowing the progress of E-catalog procurement in the Government Procurement of Goods/Services process in accordance with the Goals and Policies and Principles of Procurement of Goods /Government Services. The subjects in this research were all regional apparatus within the Kampar Regency Government. Data analysis is quantitative which is used to process data sourced from Electronic Catalog (e-Monev) publication data and the General Procurement Plan Information System (SiRUP) of the Government Goods/Services Procurement Policy Institute and the Goods/Services Procurement Section of the Kampar Regency Regional Secretariat.